Rancang Bangun Mesin Pencetak Bakso - Nofrinaldi Saputra Saputra; Muchlisinalahuddin Muchlisinalahuddin; Armila Armila (Politeknik Negeri Padang, 2022)
This research to design a smaller and easy to operate meatball maker machine. This design will simplify, speed up and minimize the energy expended in the meatball maker machine. Simulation of frame strength using Solidwork 2018. The simulation value of von Mises stress on the frame is with a maximum stress of 10,550,430.00 N/m2 and a minimum of 90,629 N/m2 with a yield strength of 250,000,000.00 N/m2. Displacement in the simulation of displacement is with a maximum value of 0.154 mm and a minimum of 0.000 mm. The value of the safety factor from the simulation results is 24. Static simulation results of the strength of the meatball printing machine frame using ASTM A36 Steel L 30 mm x 30 mm 3 mm thick with a load of 25 kg, the frame is able to withstand engine performance during operation.